Direito penal do inimigo e a corrosão simbólica do garantismo penal - Dornelas, Gabriel Barroso (2019)
The present work aims to understand the relationship that the media has with criminal recrudescence as a way of solving Brazilian crime, as well as conducting a brief analysis of the anti-crime project, verifying its proximity to the guarantor model or a punitivist model. Therefore, it is necessary to analyze which penal model Brazil has adopted throughout its history. Given the above, the intends to carry out an analysis of the influence of the media and the solutions taken by the legislator to solve the Brazilian criminal problem, make a comparison between the Guarantee Theory defended by Lugi Ferrajoli, and the model adopted in Brazil, as well as verify the anti-crime project, which appears as a promise to fight crimes of “corruption”, if this solution breaks with the already established models or appears as a simplistic solution that is commonly adopted by our legislator.